Partisipasi Masyarakat Pada Pemilihan Umum Tahun 2019-2024 Menurut Tinjauan Fikih Siyasah (Studi Kasus Di Nagari Tiku Selatan Kabupaten Agam) - Adi Jumanda; Ferdi Yufriadi; Donna Ramadhan Fitri; Irvan Refliandi (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2023)
The purpose of this study is to evaluate the extent of community involvement in the general elections of 2019-2024 using the perspective of fiqh siyasah. This study was conducted in Nagari Tiku Selatan, Agam Regency. The main objective of this research is to understand the factors influencing voter participation in the context of general elections and the extent to which the principles of fiqh siyasah play a role in this process. This research adopts a qualitative descriptive method as the primary data collection and analysis approach. Data were obtained through documents, observations, and interviews selected representatively from the community of Nagari Tiku Selatan. The results of the research indicate that there are contributing factors to the low level of participation in general elections in Nagari Tiku Selatan. These factors include economic aspects, employment situations, and the level of community awareness. On the other hand, this research also reveals the relevance of the principles of fiqh siyasah, particularly the principle of consultation or "shura," in the context of political participation in Islam. However, the passive attitudes and actions of the community in general elections are considered inconsistent with Islamic teachings that encourage participation in choosing leaders. This research provides valuable insights into community participation in general elections and emphasizes the importance of understanding the factors influencing political participation. The implications of this research can be used as a basis for designing more effective strategies to enhance community participation in future election processes.